Popularity-Aware and Diverse Web APIs Recommendation Based on Correlation Graph - Wu, Shengqi; Shen, Shigen; Xu, Xiaolong; Chen, Ying; Zhou, Xiaokang; Liu, Dongning; Xue, Xiao; Qi, Lianyong (IEEE transactions on computational social systems, 2023)
The ever-increasing web application programming interfaces (APIs) in various service-sharing communities (e.g., ProgrammableWeb.com and Mashape.com) have enabled software developers to quickly create their interested mashups conveniently and economically. However, the big volume of candidate web APIs and their differences often make it hard for software developers to discover a set of appropriate web APIs for mashup creation by considering API functions and API quality performances (e.g., popularity, compatibility, and diversity) simultaneously. These decrease the mashup development success rate and the mashup developers' satisfaction significantly. In view of these challenges, a novel web APIs' recommendation method named the popularity-aware and diverse method of web API compositions' recommendation (PD-WACR) is proposed in this article. In concrete, we model web APIs' functions, popularity, and compatibility with an API correlation graph. Afterward, correlation graph-based web APIs' recommendation is performed with popularity and compatibility guarantee. Moreover, a top- k strategy is adopted in the recommendation process, so as to diversify the final recommended web APIs' results. Finally, massive experiments are carried out on a real-world web API dataset crawled from ProgrammeableWeb.com. Experimental comparisons with related methods show the advantages and innovations of the proposed PD-WACR method.